COST ANALYSIS BY STANDARDS IN THE ACCOUNTS. - Rucker, Ranald G. (The Accounting Review, 1939)
A basic concept of cost accounting is necessary before one attempts to evaluate a particular type of cost-accounting system. Varying and narrow concepts of the function of cost accounting cause much of the controversy as to the relative merits of the various systems. As a starting point, it may be said that cost accounting is not a separate and distinct field, but is merely a phase of the general accounting. A cost-accounting system should "tie in" or be coordinated with the general accounting system, for both are concerned with the transactions and status of a single business entity which operates for the purpose of making a profit. The function of accounting, in a broad sense, is to furnish interested parties with certain information when it is needed. This function may be viewed from the uses to which the information is put. Among them are the following: 1) pricing policy of product; 2) other policy formation; 3) preparation of periodic statements; 4) control of operations with the object of securing efficient production. The relative importance of the various uses of cost data will vary greatly with the type of industry, size of the business, and other circumstances; but management realizes that there are various possible uses and makes such use of cost data as circumstances necessitate.